Correlation Between Vulva Hygiene And Intrauterine Device Use And The Event Of Vaginal Discharge In Women Of Reproductive Age - Petri Damiani; Ade Dharmawan; Nicolas Layanto; Donna Mesina Rosadini Pasaribu (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2023)
Pathological leucorrhoea is an abnormal disorder in women of childbearing age that occurs in the body in the form of thick white, yellowish, greenish discharge. This is because the composition of the vaginal microflora fluctuates as a function of internal factors such as age,hormonal changes during menarche,menstruation,and pregnancy. External factors such as hygiene practices, sexual relations, and contraceptive use.In the use of Intrauterine devices, there is vaginal discharge that occurs as a result of the initial reaction to the presence of a foreign body, the use of intrauterine contraceptives which can change the chemical balance of the vagina and is thought to cause vaginitis. The research method for this literature review analyzed 8 research articles and assessed the articles based on predetermined inclusion and exclusion criteria. This literature reviews various risk factors that influence the occurrence of vaginitis due to the use of non-hormonal intrauterine contraceptive devices that occur in women of childbearing age and through good vulva hygiene behavior,can reduce the risk of physiological and pathological vaginal discharge.Based on these sources,it can be concluded that there is a relationship between vulva hygiene and the use of Intrauterine device with the incidence of vaginal discharge in women of childbearing age.